Tutela jurisdiccional efectiva en el proceso contencioso administrativo peruano: principales problemas y posibles soluciones - Prado Bringas, Rafael (2023)
The article analyzes the effective judicial protection in the Peruvian administrative litigation process, focusing on a new binding precedent from the Supreme Court of Justice. To that end, problems and solutions are addressed, such as the equality of sectoral regulations and the prohibition of incorporating different legal arguments in the administrative sphere. The importance of interpreting the administrative litigation process to enforce the rights of the administrators is highlighted. The duty of judges to guarantee due administrative procedure is emphasized, and a systematic interpretation of the limitation on the presentation of evidence is proposed.